Etiologic and differential diagnostic significance of tumor location in the supraclavicular fossa. (20th July 2017) - Franzen, Achim; Günzel, Thomas; Buchali, Andre; Coordes, Annekatrin
Abstract : Objective: Patients presenting with a cervical mass are common for head and neck specialists and present a diagnostic challenge against the backdrop of a wide variety of etiologies. The objective of the present study was to evaluate the significance of a mass in the supraclavicular fossa for etiology, diagnostic procedure, and therapy. Study Design: Individual retrospective cohort study. Methods: We reviewed the data of 211 consecutive cases (116 male, 95 female) with excisional biopsy or tumor removal of a supraclavicular mass. Results: In 202 of 211 cases, a biopsy was taken from a lymph node. In 182 biopsies, a malignant lymphadenopathy was found (117 metastases, 65 malignant lymphoma). The histologic findings of metastatic diseases were adenocarcinoma (48), followed by squamous cell carcinoma (22). The majority of primary carcinomas were located below the clavicle (94), in the lung (32), in the breast (29), and in the head and neck region (18). In the left supraclavicular fossa, only metastases of the genitourinary tract were significantly more frequent (16 of 17). In nonmalignant tumors (29), tuberculosis (11) was most prevalent. In 79% of biopsies, the neck mass was the first manifestation of the disease. Conclusion: The location of a cervical mass in the supraclavicular fossa provides a strong indication of malignancy. A biopsy is mandatory in the majority of patients presenting with a supraclavicular mass. In cases of metastatic disease, the location of a cervical mass helps identify the primary site. Histologic findings are essential for further diagnostic steps, therapy, and prognosis. Level of Evidence: 4. Laryngoscope, 128:646–650, 2018